P945 Should children, with exercise induced intra-ventricular gradients, be treated with beta blockers?. (17th January 2020) - Cotrim, C; Joao, I; Guardado, J; Cordeiro, P; Sampaio, M ANA; Marques, A; Cafe, H; Martins, R; Cotrim, H; Baquero, L
Abstract: Background: In our experience, treadmill exercise echocardiography (SE) is feasible and safe in children (C). Regional wall motion abnormalities (RWMA) are of limited usefulness, but Doppler often - (in 39% from 258 previously studied C) - documents significant intraventricular gradients (IVG), occult at rest, and allowing to document a possible explanation for exercise related symptoms, or abnormal resting or stress-ECG findings. Purpose - To assess the effect of ß blockers on the occurrence of IVG, in C, with symptoms or abnormal resting or stress-ECG findings. Methods – We repeated SE in 66 of the 101 C – (with normal echocardiogram at rest) - that developed IVG on exertion, under treatment with ß blockers. These 66 C who repeated the SE under treatment with ß blockers are the study group. 15 (23%) of them were female and the mean age of the group was 14, 6 ± 1, 7 years old (11 to 17). They all underwent SE with 2D and Doppler echocardiographic evaluation of, and during treatment with ß blockers. Results: Mean IVG in those 66 C submitted to SE was 105 ± 38 mmHg in the first SE evaluation. In SE evaluation performed under ß blockers, 37 of them didn't develop IVG and in 29 of them IVG was significantly reduced to a mean IVG of 58 ± 32 mmHg (p< 0, 0001). The mean heart rate attained at peak exercise was 178 ± 15 bpm in the first SE evaluation and 157 ± 9 bpm in the evaluation performed under treatment with ß blockers (p < 0, 0001). 47 of these C reproduced clinical symptoms (that were indication to SE) of beta-blockers, and only 7 reproduced the symptoms under treatment with beta blockers (p< 0, 0001). Conclusions: In C with symptoms, abnormal rest or exercise ECG on medical evaluation and IVG on exertion, treatment with oral ß blockers prevented the occurrence of IVG or significantly reduced its magnitude. These changes were associated to significant clinical improvement in 85 % of the symptomatic population.